2010
DOI: 10.1007/s11250-010-9706-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of sheep breeds from Southern peninsular and Eastern regions of India

Abstract: Information is presented on the genetic diversity and relationship among six Indian sheep breeds/populations belonging to the Southern peninsular and Eastern agroecological zones, based on microsatellite markers. Parameters of genetic variation, viz., allele diversity, observed heterozygosity, gene diversity and population inbreeding estimates, were calculated for the six breeds. The allele diversity ranged from 6.40 to 7.92, whereas the gene diversity varied from 0.617 to 0.727. The highest allele and gene di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
(39 reference statements)
0
14
3
Order By: Relevance
“…The total allele numbers, mean allele number per locus, effective number of alleles, and mean heterozygosity (0.87) observed in 17 microsatellite loci were higher than those reported in the literature (16)(17)(18)(19)(20)(21)(22)(23)(24). These findings indicate that the used microsatellite markers can be reliably used to measure genetic diversity for these breeds.…”
Section: Discussioncontrasting
confidence: 54%
“…The total allele numbers, mean allele number per locus, effective number of alleles, and mean heterozygosity (0.87) observed in 17 microsatellite loci were higher than those reported in the literature (16)(17)(18)(19)(20)(21)(22)(23)(24). These findings indicate that the used microsatellite markers can be reliably used to measure genetic diversity for these breeds.…”
Section: Discussioncontrasting
confidence: 54%
“…Marked differences were observed in the morphological traits of the sheep breeds in this study. The present values of BW and linear body measurements of Yankasa, Uda and Balami sheep are higher than the range of values reported for Ganjam sheep in India by Arora et al [10]. Most researchers consider an organism’s phenotype as a multivariate set of variables and the covariation of traits an important analytical consideration [22].…”
Section: Discussionmentioning
confidence: 71%
“…However, the values fall within the range reported for other sheep breeds. Arora et al [10] reported values for observed number of alleles in the range of 7 and 25 with a mean value of 13.96. The small average number of alleles per locus in Uda and WAD may be the result of a small number of founder animals since the degree of genetic variability among these animals will be small even in the presence of crossbreeding and mutation rates [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations